Synthesis, structure and magnetic properties of the series of compounds Yb2ZrxTi2xO7 - Lieberich, Francisco (2023)
The series of novel compounds Yb2ZrxTi2xO7, with composition ranging from x = 0.0 to x = 2.0, were synthesized by the solid-state reaction and by the sol-gel method. The structures of the compounds were investigated using x-ray diffraction, Raman spectroscopy and electron microscopy. Pure phase samples could not be synthesized by the solid-state reaction, except for Yb2Ti2O7. The sol-gel samples did form pure phases, although with an increased degree of structural disorder. Along the Yb2ZrxTi2xO7 series the structure ranges from an ordered pyrochlore, for x 0.5, to a disordered fluorite, for x = 1.0, 1.5, and finally to the rhombohedral -phase, for x = 2.0. The morphotropic transition from pyrochlore to fluorite occurs in the range 0.5 < x < 1.0, somewhat less than the value predicted by the structural tolerance factor, x = 1.21. The intermediate compositions, close to the morphotropic phase boundary, exhibit either structural distortions or short-range local order that does not extend to the long-range crystal structure. Low temperature magnetization and AC magnetic susceptibility measurements were used to characterize the magnetic ground state of these magnetically frustrated compounds. The transition to long range magnetic order is suppressed with increasing structural disorder, suggesting an increase in magnetic frustration and possible stabilization of a spin liquid ground state for Yb2Zr2O7.